Clinical neurological characteristics of ischemic stroke subtypes in acute phase - Shkrobot, S. I.; Sokhor, N. R.; Milevska-Vovchuk, L. S.; Krynytska, I. Ya.; Marushchak, M. I.; Shkrobot, L. V.; Yasnij, O. R. (Zaporozhye Medical Journal, 2018)
Objectives. The aim of the present study was to clarify clinical neurological characteristics and different ischemic stroke subtypes unfavorable course predictors in acute phase. Material and Methods. 482 patients with different ischemic stroke subtypes were observed. Among them there were 125 (25.9 %) with cardioembolic infarct (CEI), 119 (24.7 %) with large artery atherosclerosis (LAAS) infarct, 122 (25.3 %) with lacunar stroke (LAC), 116 (24.1 %) with stroke of undetermined etiology (UDE). The comparative analysis of clinical picture was performed. The predictors of unfavorable course of acute phase were established. Results. We have found out that severe neurological deficit, high mortality and the worst functional outcome during the first 14 days were observed in patients with CEI and LAAS. The highest frequency of early neurological deterioration (END) was detected at LAC (in 22.7 % of patients). There was a relationship between END and presence of transient ischemic attack (TIA) in past medical history, the level of systolic blood pressure (SBP) at the beginning of the disease and the degree of carotid arteries stenosis on the side of lesion. The patients with LAC had mild neurological deficit and better prognosis compared with other ischemic stroke subtypes. Among the clinical factors that have impact on the CEI, LAAS and UDE acute phase course were: the size of lesion, the level of consciousness on the 1st day, the baseline SBP, patient’s age. At LAAS, the presence of transient ischemic attack (TIA) in past medical history and low SBP in the onset of the disease (less than140 mm Hg) has an additional prognostic value for an unfavorable functional outcome. The severity of LAC in acute period depended on its localization and size. Localization of LAC in the internal capsule, thalamus and pons were characterized by the highest severity. Conclusions. Clinical neurological features of ischemic stroke depend on its subtype and have some prognostic value for the course of different ischemic stroke subtypes in acute phase.